Trade-Unions in an Age of Pluralism and Structural Change : The Response to the Irrepressible Demands of the Common Man - Barkin, Solomon (Relations industrielles / Industrial Relations, 1971)
Reviewing the industrial unrest of the last three years in Western Europe and the United States, the author describes and analyses the new trends in the trade-union movement to cope with such a new situation.